2020
DOI: 10.1007/s11356-020-09967-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the ecological and human health risks from metals in shrimp aquaculture environments in Central Java, Indonesia

Abstract: The occurrence and contamination level of seven important toxic metals (Cd, Cu, Co, Cr, Hg, Pb, and Zn) and three additional metals (Al, Fe, and Mn) in the water, sediment, and shrimp muscle in aquaculture areas located in Central Java, Indonesia, were investigated. The results suggest that the majority of metals have higher concentrations in the inlet followed by the outlet and ponds. Cd dissolved in the waters exhibited the highest level in Pekalongan (3.15 ± 0.33 μg L −1). Although Pb was not detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 111 publications
1
14
1
Order By: Relevance
“…Notwithstanding, a key issue regarding metal accumulation and eventual harmful effects on mangrove biota depend on metal abundance and availability (Marchand et al, 2011;Lacerda et al, 2020). Unfortunately, no study to our knowledge has observed the effects of aquaculture derived trace metals on mangroves and this is an urgent necessity in view of the rapid expansion of the activity and the high metal-complexing capacity of dissolved C present in shrimp farming effluents (Lacerda et al, 2006a(Lacerda et al, ,b, 2011Hidayati et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding, a key issue regarding metal accumulation and eventual harmful effects on mangrove biota depend on metal abundance and availability (Marchand et al, 2011;Lacerda et al, 2020). Unfortunately, no study to our knowledge has observed the effects of aquaculture derived trace metals on mangroves and this is an urgent necessity in view of the rapid expansion of the activity and the high metal-complexing capacity of dissolved C present in shrimp farming effluents (Lacerda et al, 2006a(Lacerda et al, ,b, 2011Hidayati et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Harmesa et al (2021 reported that the Cd concentration in Dasun estuary, Rembang was relatively high, and the source was presumed to be waste from the batik industry. Pb concentration ranged from 7.6 to 15.40 mg kg −1 dw in shrimp aquaculture in Central Java and showed moderate contamination, according to the ecological risk (geoaccumulation index (Igeo), contamination factor (CF), pollution load index (PLI), and potential ecological risk index (PERI)) determined in the sediments (Hidayati et al, 2020). The average Cd compositions ranged from 0.13 to 0.89 mg/kg, while the average Cr compositions ranged from 0.09 to 96.0 mg/kg, according to the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surface water samples were collected in August 2017 during the dry season at three different sites in each pond, i.e., the inlet, pond, and outlet. The inlet samples were collected before water entered the pond; the pond samples were collected inside the pond, while the outlet samples were collected from a site after the discharge gates (Hidayati et al, 2020). In the present study, we also collected water samples from 20 nonaquaculture sites.…”
Section: Sample Collection and Analysismentioning
confidence: 99%